UJI AKTIVITAS ANTIPIRETIK EKSTRAK ETANOL DAUN SAWI PAKCOY (Brassica rapa Linn.) TERHADAP MENCIT PUTIH (Mus musculus L.) JANTAN YANG DI INDUKSI PEPTON 5% - Sulastri Herdaningsih; Iis Maghfira Aulia (Jurnal Komunitas Farmasi Nasional, 2026)
Fever is a condition marked by an increase in body temperature beyond normal limits. This study aims to evaluate the antipyretic effect of ethanol extract from pakcoy mustard leaves (Brassica rapa Linn.) on male white mice (Mus musculus L.) induced with 5% peptone and to determine the effective dose of the extract. Fifteen male mice were divided into five groups: negative control (0.5% Na-CMC), positive control (paracetamol 65 mg/kg body weight), and three treatment groups receiving ethanol extract doses of 100 mg/kg, 200 mg/kg, and 400 mg/kg body weight. All groups were induced using 5% peptone subcutaneously until a rectal temperature increase of ≥0.6°C occurred, followed by oral administration of the test substances. Temperature was recorded every 30 minutes over 4 hours. Statistical analysis revealed significant antipyretic effects in all treatment groups compared to the negative control (p values 0.02, 0.01, 0.04; p < 0.05) at doses 100, 200, and 400 mg/kg body weight respectively. The findings suggest that ethanol extract of pakcoy mustard leaves possesses significant antipyretic activity in male white mice induced with fever. Keywords: Pakcoy Mustard (Brassica rapa Linn.), Antipyretic, White Mice (Mus musculus L.)